Shade a novel - Jordan, Neil 1950- (Bloomsbury, 2004)
Nina Hardy, murdered by her childhood friend, George, watches and retells the events of her life and afterlife, as her half-brother retraces their childhood together, revealing the crime against Nina in all its full and heartbreaking meaning.
Keywords: Funeral rites and ceremonies -- Fiction; Murder victims' families -- Fiction; Murder victims -- Fiction; Friendship -- Fiction; Irland; Ireland -- Fiction; Psychological fiction; Fiktionale Darstellung